2. Work in Progress: PhD Thesis. Boiotia Through the Eyes of a Boiotian. The Depiction of Boiotia in Plutarch’s Corpus - Una Markham (Teiresias Journal Online, 2024)
Una MARKHAM (University of Reading) PhD Thesis: Boiotia through the Eyes of a Boiotian. The Depiction of Boiotia in Plutarch's Corpus